Orthodontic tooth movement with and without corticotomy - A study realized on animal model - Irinel Panainte; Eugen Bud; Manuela Chibelean; Mahmoud El Saafin; Irina Zetu; Delia Elena Daragiu; Mariana Pacurar (Amaltea Medical Publishing House, 2022)
Orthodontic treatment of dento-maxillary anomalies is a common therapeutic intervention, with a growing number of pediatric and adult patients requiring it [1]. The raising understanding of the need for this treatment option has led to a shift in the addressability of various social groups, leading to an increase in adult patients' interest [2]. Orthodontic treatment in adult patient is more dificult because the bone remodeling is hard to do and thereis not growing process. Cortiotomy consists of milling the alveolar bone, the vestibular board, in order to create small labor in which the dental displacement following the application of orthodontic force will be faster. The corticotomy is performed in local anesthesia, with bone cutters, under continuous cooling with saline. Orthodontic treatment in adult patient is more difficult because the bone remodeling is hard to do and thereis not growing process [3]. Filho et al. said that the introduction of this technique of corticotomy makes it possible to solve complex cases while providing an alternative to the classical approach, eliminating a number of inventients, such as dental extractions [4]. Despite the many benefits it can bring when it is integrated into orthodontic therapy to correct various dento-maxillary changes, the corticotomy is still regarded with some reluctance by orthodontists. Reitan et al. (2015) consider that the main reason is that the intervention is expensive and some consider it invasive [5]. In a similar study, Bos et al. (2005) points out that even for patients, the high costs of such an intervention can lead to its refusal, with the risk of obtaining results at the end of less satisfactory orthodontic treatment [1]. Dab et al. (2007) states that there is a direct link between the degree of dental displacement induced by the corticotomy and the type of dento-maxillary anomaly that needs to be corrected, but also the time of orthodontic treatment in which the surgery is performed [6]. Further experimental studies are also needed to understand in more detail the biological mechanisms and transformations that occur at the intervention level.